Using decision analysis to develop a framework for nest protection for threatened birds - Joy S. Tripovich; Terry Walshe; Andrew Elphinstone; Dean Ingwersen; Mick Roderick; Benjamin J. Pitcher (Oryx)
The regent honeyeater Anthochaera phrygia is a Critically Endangered Australian songbird, with current population estimates of < 300 individuals remaining in the wild. Low nest success is a factor preventing the recovery of the population, and management remedies are needed. However, a lack of data on intervention success raises uncertainty and impedes planning. To identify management priorities under uncertainty, we engaged with conservation practitioners and key stakeholders to develop and evaluate potential nest protection interventions. Four categories of threats were considered: avian predators, mammalian predators, extreme weather events and avian competitors. The interventions with the highest predicted probabilities of nest success under each threat category were, respectively: lethal control of avian predators, the use of tree collars to control arboreal mammalian predators, the provisioning of supplementary food and nesting resources during extreme weather events, and control of the noisy miner Manorina melanocephala, a competitor species. Our analysis shows that by applying a combination of conservation actions alongside improvements in nest detection, it is possible, based on the opinion of experts, to provide a pathway for the recovery of the regent honeyeater.